Control of stepper motor driven differential drive robot for tracking waypoint trajectories: modeling, simulation, optimization and experimental investigations. (4th May 2021) - Mathew, Robins; Hiremath, Somashekhar S.
ABSTRACT: Waypoints are abstract points through which the robot has to be controlled to reach the goal. Waypoint-based robot control can be used as an alternative to continuous trajectory control. This paper discuses the implementation of a waypoint tracking kinematic controller along with a dynamic slip avoidance controller on a stepper motor driven differential drive robot. The dynamic controller utilizes torque limiting strategy to avoid wheel slip that will occur when trajectory tracking is carried out with a kinematic controller alone. Optimization of control parameters is carried out using multi-objective particle swarm optimization technique to minimize trajectory tracking error as well as velocity tracking error. The controller is designed to take care of different velocity constrains on the robot so that it can be employed on a real robot. The controller developed in this work is tested for tracking different waypoint trajectories. The trajectory tracking results are compared with the result of robot control with a kinematic controller. The results show improvement in trajectory tracking, and in velocity tracking.